Acenequinocumulenes: Lateral and vertical π-extended analogs of tetracyanoquinodimethane (TCNQ) - Gruber, Marco; Padberg, Kevin; Min, Jie; Waterloo, Andreas; Hampel, Frank; Maid, Harald; Ameri, Tayebeh; Brabec, Christoph; Tykwinski, Rik (Chemistry - A European Journal, 2017)
We have designed a series of molecules and developed synthetic methodology that allows for the inclusion of structural diversity along both the lateral and vertical axes of the basic TCNQ skeleton. In the lateral direction, benzoannulation extends the π-system through (hetero)acene formation, while incorporation of a [3]cumulene increases delocalization vertically. The potential of these new molecules as semiconductors is explored through UV-vis spectroscopy, cyclic voltammetry, X-ray crystallography, thin film formation, and mobility measurements (via space charge limited current measurements
Keywords: pentacenes; donor-acceptor; organic materials; cumulenes; synthetic methodology

Acenes with a click - Waterloo, Andreas; Kunakom, Sylvia; Hampel, Frank; Tykwinski, Rik (Macromolecular Chemistry and Physics, 2012)
A protected pentacene precursor is functionalized in the 6- and 13-positions with alkyne groups and subsequently derivatized by a copper-catalyzed azide-alkyne Huisgen cycloaddition (CuAAC) reaction. Aromatization then gives the desired pentacene derivatives. This method offers an expedient route to a range of bench-top stable, pentacene, and oligopentacene based chromophores, all derived from a single building block. These new pentacene derivatives are characterized by NMR, IR, and UV-Vis spectroscopies. X-ray crystallographic data for two derivatives is used to evaluate the prospect of electronic communication in the solid state via π-stacking interactions. Full Paper: The CuAAC reaction of azides with a protected pentacene precursor is developed to formally establish compatibility of this powerful reaction with the conjugated pentacene chromophore. Alkyl, aryl, heteroaryl, and oligomeric azides are successfully used. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Allenylidene complexes based on pentacenequinone - Strinitz, Frank; Waterloo, Andreas; Tucher, Johannes; Huebner, Eike; Tykwinski, Rik; Burzlaff, Nicolai (European Journal of Inorganic Chemistry, 2013)
Stable ruthenium-allenylidene complexes based on pentacenequinone have been synthesized. The complexes show an electronic absorption in the NIR region that arises from forbidden MLCT transitions, as explained by DFT calculations. The crystal structure reveals promising features for the formation of metal-influenced organic FETs. Stable ruthenium-allenylidene complexes based on pentacenequinone have been synthesized. The depicted complex shows an electronic absorption in the NIR region that arises from forbidden MLCT transitions, as explained by DFT calculations. The crystal structure reveals promising features for the formation of metal-influenced organic FETs. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

An unsymmetrical pentacene derivative with ambipolar behavior in organic thin-film transistors - Tykwinski, Rik; Etschel, Sebastian; Halik, Marcus; Jäger, Christof; Clark, Timothy; Margraf, Johannes; Waterloo, Andreas; Hampel, Frank; Yousefi Amin, Atefeh (Chemical Communications, 2013)
Three new unsymmetrical anthracenyl-pentacene derivatives have been synthesized, characterized using X-ray crystallography, and used as semiconductors in OTFTs. For one derivative, ambipolar charge carrier transport was observed with a hole mobility of 0.2 cm V s and an electron mobility of 0.03 cm V s. © 2013 The Royal Society of Chemistry.

Aryl substitution of pentacenes - Waterloo, Andreas; Sale, Anna Chiara; Lehnherr, Dan; Hampel, Frank; Tykwinski, Rik (Beilstein Journal of Organic Chemistry, 2014)
A series of 11 new pentacene derivatives has been synthesized, with unsymmetrical substitution based on a trialkylsilylethynyl group at the 6-position and various aryl groups appended to the 13-position. The electronic and physical properties of the new pentacene chromophores have been analyzed by UV-vis spectroscopy (solution and thin films), thermoanalytical methods (DSC and TGA), cyclic voltammetry, as well as X-ray crystallography (for 8 derivatives). X-ray crystallography has been specifically used to study the influence of unsymmetrical substitution on the solid-state packing of the pentacene derivatives. The obtained results add to our ability to better predict substitution patterns that might be helpful for designing new semiconductors for use in solid-state devices.
EAM Import::2019-03-13

Axial coordination of pyridyl-containing pentacenes to porphyrins - Waterloo, Andreas; Lippert, Rainer; Jux, Norbert; Tykwinski, Rik (Journal of Coordination Chemistry, 2015)
A pair of pentacenes that are functionalized in the 6-position with either a 3- or 4-pyridyl group via a triazole linker have been used to form complexes with a tetra(aryl)ruthenium(II) porphyrin through axial coordination. The pentacene–porphyrin dyads 5 and 6 have been structurally characterized through a combination of spectroscopic techniques. UV–vis spectroscopy shows that the absorption profiles of the two chromophores, the porphyrin and the pentacene, are complementary, providing absorptions throughout the UV and visible regions. While the dyads are reasonably stable in the solid state under ambient conditions they are, unfortunately, only stable in solution for hours when exposed to light and air.
EAM Import::2019-03-13

Carbon-rich cyclopentadienyl ruthenium allenylidene complexes - Spörler, Susanne; Strinitz, Frank; Rodehutskors, Philipp Maximilian; Müller, Lisa; Waterloo, Andreas; Dürr, Maximilian; Hübner, Eike; Ivanovic-Burmazovic, Ivana; Tykwinski, Rik; Burzlaff, Nicolai (New Journal of Chemistry, 2016)
Ruthenium allenylidene complexes with carbon-rich polyaromatic moieties have been synthesized by using [RuCl(η-CH)(PPh)] (η-CH = cyclopentadienyl) as a precursor and the propargyl alcohols 10-ethynyl-10-hydroxyanthracen-9-one (ACO), 13-ethynyl-13-hydroxypentacen-6-one (PCO), 1-phenyl-1-(pyren-1-yl)prop-2-yn-1-ol (PyrPh), 9-ethynyl-9H-fluoren-9-ol (FN) and 6-ethynyl-6H-benzo[cd]pyren-6-ol (BPyr) as ligands. The resulting cationic allenylidene complexes, [Ru(η-CH)(CC(AO))(PPh)]PF (1), [Ru(η-CH)(CC(PCO))(PPh)]PF (2), [Ru(η-CH)(CC(PyrPh))(PPh)]PF (3), [Ru(η-CH)(CC(FN))(PPh)]PF (4), and [Ru(η-CH)(CC(BPyr))(PPh)]PF (5) show interesting intermolecular π-interactions in the solid-state structure as well as solution state complexation with pyrene (documented by Job's plots experiments). CV data indicate possible Ru(ii)/Ru(iii) oxidation, as well as the potential reduction of the carbon-rich allenylidene moiety.

Intermolecular Singlet Fission in Unsymmetrical Derivatives of Pentacene in Solution - Casillas Pacheco, Ruben; Adam, Matthias; Brana Coto, Pedro; Waterloo, Andreas; Zirzlmeier, Johannes; Reddy, Seelam Rajagopala; Hampel, Frank; Mcdonald, Robert; Tykwinski, Rik R.; Thoss, Michael; Guldi, Dirk Michael (Advanced Energy Materials, 2019)
Intermolecular singlet fission (SF) is an electronically coupled process between two chromophores, where distance dependences are decisive in terms of rates and yields. In the current work, a family of pentacene derivatives featuring different functional groups have been designed, synthesized, and probed with respect to intermolecular SF in the low, medium, and high concentration regimes rather than in the solid state. By means of advanced photophysical techniques, global analysis modeling, and ab initio calculations, a model for intermolecular SF is postulated. The model is based on an early key intermediate, which involves the diffusional encounter between one pentacene in its singlet excited-state with another one in its ground state and which features excimer characteristics. This is followed by a transformation into a coupled triplet excited-state. The role of the functional group appended to pentacene is analyzed with respect to steric shielding of the pentacene core as a means to prevent photophysical degradation, as well as control diffusional encounter and, subsequently, SF. The findings demonstrate the potential of new molecular materials for SF, especially in solution studies, as well as the challenges of implementing them in energy conversion schemes due to the appearance of photodegradation processes that compete with SF.
CRIS-Team WoS Importer:2019-02-21

Isomerically pure syn-anthradithiophenes: Synthesis, properties, and FET performance - Lehnherr, Dan; Waterloo, Andreas; Goetz, Katelyn P.; Payne, Marcia M.; Hampel, Frank; Anthony, John E.; Jurchescu, Oana D.; Tykwinski, Rik (Organic Letters, 2012)
The synthesis of isomerically pure syn-anthradithiophene derivatives (syn-ADTs) is described. X-ray crystallography is used to compare the solid-state arrangement of syn-ADT derivatives 2a,b to the analogous mixture of syn- and anti-ADTs. Single-crystal OFETs based on isomerically pure syn-ADTs 2a,b display device performance comparable to those based on a mixture of ADT isomers syn/anti-2a,b with mobilities as high as 1 cm /(V s). © 2012 American Chemical Society.